Effect on Morphine Requirement of Early Administration of Oral Acetaminophen vs. Acetaminophen/Tramadol Combination in Acute Pain. Issue 3 (4th February 2019) - Bouida, Wahid; Beltaief, Kaouthar; Msolli, Mohamed Amine; Ben Marzouk, Maryem; Boubaker, Hamdi; Grissa, Mohamed Habib; Zorgati, Asma; Methamem, Mehdi; Boukef, Riadh; Belguith, Asma; Nouira, Semir
Abstract: Objectives: To evaluate the effect on opioid requirement of pain treatment starting at triage, and to evaluate satisfaction in emergency department (ED) patients with acute pain. Methods: This is a single‐blind, randomized, prospective study conducted in the ED. The included patients were randomly assigned to single oral doses of placebo, acetaminophen, or a tramadol/acetaminophen combination. Protocol treatment was given at triage. The primary outcome was the need for rescue morphine during ED stay. The secondary outcome included patient satisfaction, ED length of stay, and percentage of patients discharged from the ED with a VAS score of <30. Results: We included 1, 485 patients: 496 patients in the placebo group, 497 in the acetaminophen group, and 492 in the tramadol/acetaminophen combination group. The groups were similar regarding demographic and clinical characteristics and baseline VAS pain scores. Rescue morphine was significantly decreased in the tramadol/acetaminophen combination group compared to that in the placebo and acetaminophen groups (11.5%, 23.2%, and 18.9%, respectively; P = 0.03). Patient satisfaction was higher in the tramadol/acetaminophen combination group (77% vs. 69% in the acetaminophen group and 68% in the placebo group). A VAS score of <30 was observed in 84% of patients in the placebo group, 83% in the acetaminophen group, and 87% in the tramadol/acetaminophen combination group ( P = 0.01 between the acetaminophen group and tramadol/acetaminophen combination group). The ED length of stay was 60 minutes for the acetaminophen group and tramadol/acetaminophen combination group and 71 minutes for the placebo group ( P = 0.04). Conclusion: Oral tramadol/acetaminophen combination administered early in triage was associated with a decrease in intravenous morphine requirement and increase in satisfaction among ED patients with acute pain when compared with patients taking acetaminophen. No significant increase in side effects was found. This intervention may be considered in EDs with an aim of similar benefits.